Transformasi Edu Literasi melalui Novel Anak: Integrasi SDGs dan Pembentukan Pola Pikir Sistemik dalam Pendidikan Guru - Arifin Alatas, Mochamad; Ahmad Putikadyanto, Agus Purnomo; Efendi, Agik Nur; Sahrul Romadhon; Liana Rochmatul Wachidah; Albaburrahim, Albaburrahim (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This study explores the implementation of children's novels as a medium to integrate Sustainable Development Goals (SDGs) values into teacher education. It aims to examine the extent to which children's novels can enhance reading interest, internalize sustainability concepts, and foster systemic thinking among prospective educators. The methods used include interviews, observations, and theoretical analysis based on Literacy Transformation, UNESCO guidelines, and a Systems Thinking approach. The findings show that the use of children's novels significantly boosts reading engagement and effectively connects theory with practice through contextual and emotional narratives. Children's novels also prove effective in fostering a deep understanding of social justice, equality, and environmental sustainability. Despite challenges such as limited teacher training and curriculum integration, the study highlights the strategic potential of children's novels in shaping critical, creative, and systemic educators. The results recommend strengthening story-based literacy programs and providing teacher training focused on integrating sustainability values to enrich learning in teacher education programs.